дидактические материалы алгебра 7 класс Звавич, Кузнецова

с-33

 

1. 1) a)(a + 3)(b - 7) = ab - 7a + 3b - 21;
б) (a - 5)(11 - b) = 11a - ab - 55 + 5b;
в) (-8 - a)(b + 2) = -8b - 16 - ab - 2a;
г) (-7 - b)(a - 7) = -7a + 49 - ab + 7b;
2) a) (x - 4)(x + b) = x2 + 8x - 4x - 32 = x2 + 4x - 32;
6) (x - 5)(9 - x) = 9x - x2 - 45 + 5x = -x2 + 14x - 45;
б) (3 + x)(-1 - x) = -3 - 3x - x2 = -x2 - 4x - 3;
г) (x - 10)(-x - 6) = -x2 - 6x + 10x + 60 = -x2 + 4x + 60;
3) a)(8 + 3x)(2y - 1) = 16y - 8 + 6xy - 3x;
б) (2a - 1)(3a + 7) = 6a2 + 14a - 3a - 1 = 6a2 + 11a - 7;
в) (3а - 2b)(2а - 3b) = 6а2 - 9ab - 4ab + 6b2 = 6a2 - 13ab + 6b2;
г) (15a + 27)(-5a - 9) = -75a2 - 135a - 135a - 254 = -75a2 - 270a - 243;
4) a) (3x2 - 1)(2x + 1) = 6x3 + 3x2 - 2x - 1;
б) (3x2 - 1) (2x2 + 1) = 6x4 + 3x2 - 2x2 - 1 = 6x4 + x2 - 1;
в) (m2 - n)(m + n2) = m + m2n2 - mn - n3;
г) (m2 - n)(m - n2) = m - m2n2 - mn + n3;
5) a) (a + 2)(a2 - a - 3) = a - a2 - 3a + 2a2 - 2a - 6 = a + a2 - 5a - 6;
б) (5b - 1) (b2 - 5b + 1) = 5b3 - 25b2 + 5b - b2 + 5b - 1 = 5b3 - 26b2 + 10b - 1;
в) (m - n + 1)(m + n) = m2 + mn - mn - n2 + m + n = m2 - n2 + m + n;
г) (m - 2n)(m + 2n - 1) = m2 + 2mn - m - 2mn - 4n + 2n = m2 - 4n2 - m + 2n;
6) a) 2(b + 1)(b + 3) = 2b2 + 6b + 2b + 6 = 2b2 + 8b + 6;
б) -8(у - 1)(у + 5) = -8y2 - 40y + 8y + 40 = -8у2 - 32y + 40;
в) b(3b + 1)(2b - 5) = 6b3 - 15b2 + 2b2 - 5b = 6b3 - 13b2 - 5b;
г) 5m(m - n)(m + 3n) = 5m3 + 15m2n - 5m2n - 15mn2 = 5m3 + 10m2n - 15mn2.

2. 1) a) (m2 - m - 1)(m2 + m + 1) = m4 + n3 + m2 - m3 - m2 - m - m2 - m - 1 = m - m2 - 2m - 1;
6) (-3n2 + 2n + 1)(3n2 + 2n - 1) = -9n4 - 6n3 + 3n2 + 6n3 + 4n2 - 2n + 3n2 + 2n - 1 = -9n4 + 10n2 - 1;
2) a) (x + 1)(x4 - x3 + x2 - x + 1) = x5 - x4 + x3 - x2 + x + x4 - x2 + x2 - x + 1 = x5 + 1;
б) (2 + а - а3 + а5)(а - 1) = 2а - 2 + а2 - а - a4 + a3 + а6 - а5 = а6 - a- а4 + а3 + a2 + a - 2;
3) a) (y + 3)(y - 5)(y2 + 2y - 15) = (y2 - 2y - 15)(y2 + 2y - 15) = y4 + 2y - 15y2 - 2y3 - 4y2 + 30y - 15y2 - 30y + 225 =
= y4 - 34y2 + 225;

6) (x + 1)(x2 - x + 1)(x6 - x3 + 1) = (x3 - x2 + x + x2 - x + 1)(x6 - x3 + 1) = (x3 + 1)(x6 - x3 + 1) =
= x9 - x6 + x3 + x6 - x3 + 1 = x9 + 1.

3. (5x - 10y)(3х - 7у) = (10у - 5х)(7у - 3x) = 5(2у - х)(7у - 3x).

4. a) (m - 1)(m + 4) = m2 + 3m - 4;   б) (а + 3)(а - 2) = a2 + а - 6.